2009
DOI: 10.3389/neuro.06.014.2009
|View full text |Cite
|
Sign up to set email alerts
|

Digital, three-dimensional average shaped atlas of the heliothis virescens brain with integrated gustatory and olfactory neurons

Abstract: We use the moth Heliothis virescens as model organism for studying the neural network involved in chemosensory coding and learning. The constituent neurons are characterised by intracellular recordings combined with staining, resulting in a single neuron identified in each brain preparation. In order to spatially relate the neurons of different preparations a common brain framework was required. We here present an average shaped atlas of the moth brain. It is based on 11 female brain preparations, each stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 68 publications
0
101
1
Order By: Relevance
“…The anti-SYNORF1 (Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, IA, USA) was raised against fusion proteins composed of glutathione-Stransferase and the Drosophila SYN1 protein (SYNORF1; Klagges et al 1996). The specificity of this antibody has been described by Klagges et al (1996), and it is reported to detect synaptic neuropil in various insect species, heliothine moths included (Berg et al 2002;Kvello et al 2009;Zhao et al 2014). After analyzing the mass-stained brains by confocal laser scanning microscopy, the preparation was rehydrated through a decreased ethanol series (10 min each) and rinsed in PBS.…”
Section: Immunostainingmentioning
confidence: 99%
“…The anti-SYNORF1 (Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, IA, USA) was raised against fusion proteins composed of glutathione-Stransferase and the Drosophila SYN1 protein (SYNORF1; Klagges et al 1996). The specificity of this antibody has been described by Klagges et al (1996), and it is reported to detect synaptic neuropil in various insect species, heliothine moths included (Berg et al 2002;Kvello et al 2009;Zhao et al 2014). After analyzing the mass-stained brains by confocal laser scanning microscopy, the preparation was rehydrated through a decreased ethanol series (10 min each) and rinsed in PBS.…”
Section: Immunostainingmentioning
confidence: 99%
“…A comparative volumetric analysis indicates that L. maderae relies more heavily on chemosensory than on visual information than all other species studied (Drosophila melanogaster: Rein et al, 2002 Kvello et al, 2009), and that L. maderae has relatively smaller optic lobes, the largest antennal lobe, and the largest mushroom body. Chemosensory input appears to be the main input to the mushroom bodies, as suggested by linear regression analysis (Table 3).…”
Section: Comparison Of the Vib-and Isa-derived Standard Cockroach Brainsmentioning
confidence: 99%
“…Selective neuropil staining by the SYNORF1 antibody has previously been demonstrated in several insect species (Brandt et al, 2005;Kurylas et al, 2008;el Jundi et al, 2009;Kvello et al, 2009). It was raised against a 66-kDa fusion protein comprising glutathione-S-transferase (GST) fused to the first amino acids of the presynaptic vesicle protein synapsin I coded by its 5 0 fragment (nucleotide sequence 621-1967, shown in Fig.…”
Section: Characterization Of Primary Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinary glomeruli in the moth AL have been analyzed in detail, and an identification method for the glomeruli has been established (Berg et al, 2002;Sadek et al, 2002;Masante-Roca et al, 2002;Greiner et al, 2004;Skiri et al, 2005;Kazawa et al, 2009;Couton et al, 2009;Varela et al, 2009), as in the cases of other insects (Galizia et al, 1999;Laissue et al, 1999). Determination of the morphology of PNs in moths by using glomeruli identification has been reported with relatively small data sets (up to 40; Sun et al, 1997;Vickers et al, 1998;Sadek et al, 2002;Kanzaki et al, 2003;Han et al, 2005;Rø et al, 2007;Kvello et al, 2009;Løfaldli et al, 2010;Zhao and Berg, 2010). In the present study, we analyzed the morphology of a total of 246 PNs, including PNs innervating ordinary glomeruli, with the glomerular identification method by using a digital atlas .…”
Section: Introductionmentioning
confidence: 99%